Persepsi Perilaku Sanitasi Masyarakat di Kawasan Semi-Perkotaan Pasca Deklarasi Open Defecation Free dengan Pendekatan IBM-WASH dan KAP - Reksa Buana; Prayatni Soewondo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Community-Based Total Sanitation (STBM) programme is the government's effort to address the issue of open defecation in Sumedang Regency, with ODF villages reaching 81.23% by 2021. Sawahdadap Village, Cimanggung District, Sumedang Regency, is a rural-urban area that has declared ODF status. The acceleration of ODF has pushed the STBM programme to continue its positive impact and complete the first pillar of STBM, which is ODF. However, this acceleration is forcing all stakeholders to achieve the target without considering the sustainability of the sanitation system afterwards. This study aims to understand perceptions of sanitation behaviour and sustainability in rural-urban areas that have declared ODF status. The EFA analysis showed that community perceptions of the societal/structural (0.684) and individual (0.501) variables contributed the most, with a total variance of 62.82% and 75% of respondents giving positive responses. The KAP analysis of stakeholder perceptions showed knowledge at 94% (SD 0.671), attitude at 87% (SD 0.827) and practice at 93% (SD 1.136), with an average KAP of 91%, confirming that stakeholder perceptions of community sanitation behaviour are good. However, Policy/Regulation (25%) and Financing/Distribution (9%) showed poor scores. Data normalisation indicates that 81% of the community has good sanitation behaviour, while the remaining 19% require additional recommendations and strategies.